Предмет:
АлгебраАвтор:
mojomcclainАвтор:
teodosiao5otАвтор:
allyson4) 0,008x³ - 27y³ = (0,2x)³ - (3y)³ = (0,2x - 3y)(0,04x² + 0,6xy + 9y²)
5) (x - 5)² = 5x² - (2x - 1)(2x + 1)
x² - 10x + 25 = 5x² - (4x² - 1)
x² - 10x + 25 = 5x² - 4x² + 1
x² - 10x + 25 = x² + 1
x² - 10x - x² = 1 - 25
- 10x = - 24
x = 2,4
Автор:
generali6kkДобавить свой ответ
Предмет:
ИнформатикаАвтор:
erikОтветов:
Смотреть
Предмет:
МатематикаАвтор:
julianneshannonОтветов:
Смотреть
Предмет:
АлгебраАвтор:
liduvinapearsonОтветов:
Смотреть
Предмет:
Русский языкАвтор:
tazОтветов:
Смотреть